Chemotherapy-induced ovarian failure in young women with early breast cancer: Prospective analysis of four randomised neoadjuvant/adjuvant breast cancer trials. (July 2021) - Furlanetto, Jenny; Marmé, Frederik; Seiler, Sabine; Thode, Christian; Untch, Michael; Schmatloch, Sabine; Schneeweiss, Andreas; Bassy, Martina; Fasching, Peter A.; Strik, Dominika; Stickeler, Elmar; Schem, Christian; et al.
Abstract: Background: Young women receiving chemotherapy for early breast cancer (EBC) have a high probability for ovarian failure, defined by chemotherapy-induced amenorrhea (CIA) as a surrogate. CIA is insufficiently reliable and reproducible. We analysed chemotherapy-induced ovarian failure (CIOF) by assessing hormone parameters, CIA, and antral follicle count (AFC). Methods: Blood samples of women aged ≤45 years treated with anthracycline/taxane-based chemotherapy for EBC from four neoadjuvant/adjuvant trials were collected at baseline, at the end of treatment (EOT), and at 6, 12, 18, and 24 months after EOT. Centrally assessed oestradiol (cutoff <52.2 ng/L) and follicle-stimulating hormone (cutoff >12.4IU/L) were used to define CIOF for patients with baseline premenopausal hormone levels, anti-Müllerian hormone (AMH), and AFC to assess ovarian reserve. Further analyses included CIA, regain of premenopausal hormone levels, and disease-free survival (DFS) also in subgroups. Results: Six hundred ninety-six patients aged ≤45 years had premenopausal hormone levels at baseline. Overall, 85.1% (592/696) experienced CIOF at EOT, and 147 of 592 had further hormone measurements after EOT. Of those, 32.7% (48/147) regained premenopausal hormone levels after 6 months, 57.9% (66/114) regained premenopausal hormone levels after 12 months, 83.0% (73/88) regained premenopausal hormone levels after 18 months, and 89.2% (74/83) regained premenopausal hormone levels after 24 months. After 24 months, 72.4% (21/29) of patients without CIOF and 100% (14/14) with CIOF had low AMH levels. Four-year DFS without CIOF versus CIOF was 65.9% versus 84.6% (hazard ratio [HR] = 2.09, 95% confidence interval [CI]: 1.37–3.19; P  < 0.001); in hormone receptor positive 61.8% versus 87.5% (HR = 2.69, 95% CI: 1.57–4.60; P  < 0.001); in <30 years 68.3% versus 92.6% (HR = 4.87, 95% CI: 1.05–22.63; P  = 0.026). Conclusion: Most premenopausal women experienced CIOF after chemotherapy for EBC. After 2 years, nearly all regain premenopausal hormone levels. CIOF was associated with better DFS, especially in patients with hormone receptor–positive EBC or aged <30 years. Highlights: We assessed chemotherapy-induced ovarian failure after therapy in women aged ≤45years. Most young women rendered postmenopausal after early breast cancer chemotherapy. After 2 years, almost three-quarters regained premenopausal hormone levels. Chemotherapy-induced ovarian failure was associated with a better disease-free survival. Each 10 unit increase in follicle-stimulating hormone after therapy was linked to an improvement in disease-free survival.